Respuesta :

Answer:

( [tex]\frac{10}{3}[/tex], - 3 )

Step-by-step explanation:

Given the 2 equations

6x - y = 23 → (1)

3y + 6x = 11 → (2)

Subtracting (2) from (1) term by term eliminates the term in x

(6x - 6x) + (- y - 3y) = (23 - 11), that is

- 4y = 12 ( divide both sides by - 4 )

y = - 3

Substitute y = - 3 into either of the 2 equations and solve for x

Substituting in (1)

6x - (- 3) = 23

6x + 3 = 23 ( subtract 3 from both sides )

6x = 20 ( divide both sides by 20 )

x = [tex]\frac{20}{6}[/tex] = [tex]\frac{10}{3}[/tex]

Solution is ( [tex]\frac{10}{3}[/tex], - 3 )